2017
DOI: 10.2217/pgs-2017-0078
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP2C19*2 Polymorphism with Clopidogrel Response and 1-year Major Adverse Cardiovascular Events in A Multiethnic Population with Drug-Eluting Stents

Abstract: Having clopidogrel HPR could be a potentially modifiable risk factor guided by phenotyping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Here, we mainly studied the association between PON-1Q192R, CYP2C19*2, CYP2C19*3 allelic variants and clopidogrel response. Several studies have been confirmed that carriers of the allelic variant (CYP2C19*2) is correlated with adverse cardiovascular events and low clopidogrel response [10,11]. whereas studies about the relevance between the allelic variant of CYP2C19*3, PON-1 Q192R and the clopidogrel response are discrepancy [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we mainly studied the association between PON-1Q192R, CYP2C19*2, CYP2C19*3 allelic variants and clopidogrel response. Several studies have been confirmed that carriers of the allelic variant (CYP2C19*2) is correlated with adverse cardiovascular events and low clopidogrel response [10,11]. whereas studies about the relevance between the allelic variant of CYP2C19*3, PON-1 Q192R and the clopidogrel response are discrepancy [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between CYP2C19 LOF alleles in patients with AMI using clopidogrel and clinical events has been studied in Northeast Asia, whereas studies in Southeast Asia are limited ( 20 , 21 ). In Taiwan, although the location was near northeast Asian, the island of Southeast Asia (ISEA) ancestry was one of the major genetic ancestries in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…The results are consistent with the Singapore cohort ( 21 ), which revealed that LOF patients were significantly more likely to experience MACE compared to non-LOF subjects in acute coronary syndrome (8.0 vs. 5.4%, p = 0.041). In patients without ACS, another smaller cohort in Malaysia recruited patients who underwent elective PCI ( 20 ). The results showed that the presence of the CYP2C19*2 polymorphism was not significantly associated with 1-year MACE after the implantation of DES.…”
Section: Discussionmentioning
confidence: 99%
“…Clopidogrel metabolizes mainly through the cytochrome P450 enzyme system in liver ( 11 ), producing active metabolites, thus inhibiting the platelet aggregation and achieving an anti-platelet effect ( 12 ). Previous findigs have confirmed that ( 13 ) CYP2C19 gene polymorphism is a major factor affecting the anti-platelet effect of clopidogrel.…”
Section: Discussionmentioning
confidence: 99%